2023
DOI: 10.1021/acs.iecr.3c00054
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Machine Learning and Redlich–Kister Theory for Solid–Liquid Equilibria Prediction of Binary Eutectic Solvent Systems

Abstract: Eutectic solvents (ESs) have gained significant interest in various chemical processes due to a broad spectrum of attractive properties, whereas their rational design is currently still in its infancy. To bridge this gap, Redlich−Kister (RK) theory and machine learning are linked for the solid−liquid equilibria (SLE) prediction of ES systems, which is thermodynamically the cornerstone for ES design. RK theory with two or three parameters is first evaluated by fitting experimental SLE of an extensive ES databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…31 Regarding the melting temperature, existing models are also trained on limited datasets primarily associated with specific types of DESs. 21,41,42 In this work, we propose more general machine learning models designed to predict the aforementioned physicochemical characteristics for various types of binary and ternary DESs. Fig.…”
Section: Data Processingmentioning
confidence: 99%
“…31 Regarding the melting temperature, existing models are also trained on limited datasets primarily associated with specific types of DESs. 21,41,42 In this work, we propose more general machine learning models designed to predict the aforementioned physicochemical characteristics for various types of binary and ternary DESs. Fig.…”
Section: Data Processingmentioning
confidence: 99%
“…93 The finally obtained model comprising 14 molecular descriptors shows a high predictive performance with a MAE of 13.89 K for T e and 0.0973 for x e . Very recently, Wang et al 533 further improved the performance of this model by employing the Redlich−Kister (RK) theory and ML methods (RF and ElasticNet). Rigorous internal and external cross-validations were carried out to develop the model (Figure 33).…”
Section: Il Mixtures−double Salt Ilsmentioning
confidence: 99%
“…Through the comparative screening, it was indicated that ESs could be considered as a superior option to ILs for the physical absorption of CO 2 . It is worth mentioning again that the RS/RK-ML models developed by Chen et al 532 and Wang et al 533 also allow the reverse design of novel ESs by estimating the SLE behaviors of different component combinations.…”
Section: Il Mixtures−double Salt Ilsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, more and more supporting databases and software are being developed and continuously improved. Up to now, QSPR has evolved from simple regression analysis to a multiple statistical ML technique, which can analyze a large scale of chemical structures. Being able to simulate the physical, chemical, and biological properties, ML-based QSPR models have been widely used to guide the development of green solvents (Table ).…”
Section: Introductionmentioning
confidence: 99%